Effect of Myrrh extract on lymph Node of Domestic Rabbit - Hamdan, Rubiel (Latakia University Journal -Biological Sciences Series, 2018)
The present study showed that myrrh has a stimulatory effect on the lymphatic node of the studied animals that are infected by gastric ulcer and external skin inflammation. This is represented by increased lymphocytes and the appearance of plasma cells which participate in defending the body . As an important components of immune system, it is also represented in the disappearance of medulary sinuses. The results of the present study also showed a decrease in lymphatic cells of lymphatic nodules of untreated animals with myrrh, specially in the medulary region. تأثير مستخلص المرة Myrrh على العقدة اللمفاوية في الأرنب الأهلي أظهرت الدراسة الحالية لمستخلص نبات المره دور محفز لوظيفة العقدة اللمفاوية عند حيوانات التجربة المصابة بالقرحة المعدية والالتهاب الخارجي، يتمثل في ازدياد عدد الخلايا اللمفاوية ، وظهور الخلايا البلازمية التي تساهم في الدفاع عن الجسم لأنها تعد من أهم مكونات الأضداد أو عوامل المناعة، واختفاء في تفاصيل الجيوب النخاعية Medulary sinuses كما أوضحت الدراسة الحالية قلة الخلايا اللمفاوية في العقدة اللمفاوية للحيوانات غير المعالجة بالمره وخاصة في المنطقة النخاعية .